Communicative versus Strategic Rationality: Habermas Theory of Communicative Action and the Social Brain - Schaefer, Michael; Heinze, Hans-Jochen; Rotte, Michael; Denke, Claudia (PLOS ONE, 2013)
In the philosophical theory of communicative action, rationality refers to interpersonal communication rather than to a knowing subject. Thus, a social view of rationality is suggested. The theory differentiates between two kinds of rationality, the emancipative communicative and the strategic or instrumental reasoning. Using experimental designs in an fMRI setting, recent studies explored similar questions of reasoning in the social world and linked them with a neural network including prefrontal and parietal brain regions. Here, we employed an fMRI approach to highlight brain areas associated with strategic and communicative reasoning according to the theory of communicative action. Participants were asked to assess different social scenarios with respect to communicative or strategic rationality. We found a network of brain areas including temporal pole, precuneus, and STS more activated when participants performed communicative reasoning compared with strategic thinking and a control condition. These brain regions have been previously linked to moral sensitivity. In contrast, strategic rationality compared with communicative reasoning and control was associated with less activation in areas known to be related to moral sensitivity, emotional processing, and language control. The results suggest that strategic reasoning is associated with reduced social and emotional cognitions and may use different language related networks. Thus, the results demonstrate experimental support for the assumptions of the theory of communicative action.